2015
DOI: 10.1016/j.jpainsymman.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Dying in the Hospital: What Happens and What Matters, According to Bereaved Relatives

Abstract: Relatives rated QOD as sufficient. A majority of patients and relatives were not sufficiently prepared for imminent death, and relatives experienced many problems. QOD appears to be a multidimensional construct, strongly affected by medical care and staff attentiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 53 publications
4
41
0
Order By: Relevance
“…The six themes elucidated in our study overlap broadly with findings from studies focused on quality of end-of-life care in other care settings, such as the general hospital ward or the ICU. 27,28 Although end-of-life care also may be provided in other settings, PCUs serve as specialized centers of excellence for such care, and thus exemplify its optimal provision in a specialized setting.…”
Section: Discussionmentioning
confidence: 99%
“…The six themes elucidated in our study overlap broadly with findings from studies focused on quality of end-of-life care in other care settings, such as the general hospital ward or the ICU. 27,28 Although end-of-life care also may be provided in other settings, PCUs serve as specialized centers of excellence for such care, and thus exemplify its optimal provision in a specialized setting.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Nonetheless, to date, few studies have explored the clinical significance of the family's presence or absence at the moment of a patient's death and meaningful communication (saying ''goodbye'') in terms of post-bereavement outcomes. 8 The primary aim of this study was to explore the potential associations between psychological outcomes on measures of depression and complicated grief on the one hand, and presence at the moment of death and meaningful communication between the patient and bereaved family members on the other.…”
Section: Introductionmentioning
confidence: 99%
“…This nding is plausible and supported by earlier surveys conducted in the United States (US), the UK, and the Netherlands, which reported that the quality of the end of life in hospitals was not satisfactory. (22)(23)(24) The main limitations of this study should be addressed. First, the test-retest was not performed.…”
Section: Discussionmentioning
confidence: 98%